Collaborative Learning in Pre-Clinical Dental Hygiene Education. - Mueller-Joseph, Laura J.; Nappo-Dattoma, Luisa (Journal of Dental Hygiene, 2013)
Purpose: Dental hygiene education continues to move beyond mastery of content material and skill development to learning concepts that promote critical-thinking and problem-solving skills. The purpose of this research was to evaluate the effectiveness of collaborative learning and determine the growth in intellectual development of 54 first-year dental hygiene students. Methods: The control group used traditional pre-clinical teaching and the experimental group used collaborative pedagogy for instrument introduction. All students were subjected to a post-test evaluating their ability to apply the principles of instrumentation. Intellectual development was determined using pre- and post-tests based on the Perry Scheme of Intellectual Development. Student attitudes were assessed using daily Classroom Assessment Activities and an end-of-semester departmental course evaluation. Results: Findings indicated no significant difference between collaborative learning and traditional learning in achieving pre-clinical competence as evidenced by the students' ability to apply the principles of instrumentation. Advancement in intellectual development did not differ significantly between groups. Value added benefits of a collaborative learning environment as identified by the evaluation of student attitudes included decreased student reliance on authority, recognition of peers as legitimate sources of learning and increased self-confidence. A significant difference in student responses to daily classroom assessments was evident on the 5 days a collaborative learning environment was employed. Conclusion: Dental hygiene students involved in a pre-clinical collaborative learning environment are more responsible for their own learning and tend to have a more positive attitude toward the subject matter. Future studies evaluating collaborative learning in clinical dental hygiene education need to investigate the cost/benefit ratio of the value added outcomes of collaborative learning.